2015
DOI: 10.1007/s13197-015-1761-z
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic processing of pigmented and non pigmented rice bran on changes in oryzanol, polyphenols and antioxidant activity

Abstract: Bran from different rice varieties is a treasure of nutrients and nutraceuticals, and its use is limited due to the poor sensory and functional properties. Application of enzymes can alter the functional and phytochemical properties. So the effect of endo-xylanase, cellulase and their combination on microstructural, nutraceutical and antioxidant properties of pigmented (Jyothi) and non-pigmented (IR64) rice bran were investigated. Scanning electron micrograph revealed micro structural changes in fibre structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Although the two methods were applied to obtain BP from IDF, the conditions were so severe that would lead to the loss of BP as well as the pollution of the environment that could not be ignored. Furthermore, enzymatic hydrolysis, which broke down cell wall to release BP, was still at its infancy with immature technology and high cost . Emerging methods represented by microwave, ultrasonic treatment, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Although the two methods were applied to obtain BP from IDF, the conditions were so severe that would lead to the loss of BP as well as the pollution of the environment that could not be ignored. Furthermore, enzymatic hydrolysis, which broke down cell wall to release BP, was still at its infancy with immature technology and high cost . Emerging methods represented by microwave, ultrasonic treatment, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Their capacity to improve functional and sensory features of food products is accompanied by the fact that their impact on the native composition is very low [ 21 ]. Regarding cereal-related products, enzymes are usually used to modify the principal component of that food, such proteins, lipids and carbohydrates [ 22 ]. In fact, in the study conducted by Prabhu et al [ 23 ], they treated rice bran with cellulase and xylanase with the aim to solubilize polyphenols with the corresponding improving of the AOC.…”
Section: Composition and Strategies For The Recovery Of Rice Bran mentioning
confidence: 99%
“…Enzymatic hydrolysis is often used to prepare cereal grains and their constituents, such as starch, protein, and bran, with the goal of enhancing their nutraceutical qualities and developing functional foods ( Prabhu and Jayadeep, 2015 ). These enzymatic techniques are claimed to improve the phenolic content and bioavailability of phenolic compounds ( Lima et al, 2018 ).…”
Section: Bioprocessing Applications To Attain Optimum Phenolic Compounds In Cerealsmentioning
confidence: 99%
“…These enzymatic techniques are claimed to improve the phenolic content and bioavailability of phenolic compounds ( Lima et al, 2018 ). However, it has also been found that the increase in phenolic content depends on the type of bran and enzyme application method used ( Prabhu and Jayadeep, 2015 ). Rice extruded with thermostable α-amylase considerably increased the retention of total phenolics from 50.85 to 87.73% compared to conventionally cooked or extruded rice.…”
Section: Bioprocessing Applications To Attain Optimum Phenolic Compounds In Cerealsmentioning
confidence: 99%